2017
DOI: 10.26740/jepk.v3n2.p170-180
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pendidikan Kewirausahaan, Locus of Control, Dan Kebutuhan Berprestasi Terhadap Pembentukan Sikap Kewirausahaan Mahasiswa

Abstract: ABSTRAKPenelitian ini bertujuan untuk menganalisis pengaruh pendidikan kewirausahaan di perguruan tinggi, locus of control, dan kebutuhan berprestasi terhadap pembentukan sikap kewirausahaan mahasiswa. Populasi dalam penelitian ini adalah mahasiswa angkatan 2012 jurusan pendidikan ekonomi FE UNESA dengan jumlah 264 mahasiswa dengan jumlah sampel sebanyak 159 orang. Teknik pengumpulan data yang digunakan yaitu kuesioner, wawancara, dan dokumentasi. Metode analisis menggunakan Regresi Linear Berganda. Hasil pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
1
5
0
5
Order By: Relevance
“…This strengthens the fact that entrepreneurial efficacy builds a mindset that fosters the Millennials' intention. Similar findings were obtained by Dwijayanti (2015) and Wirawati et al (2018). Furthermore, Wahyudiono (2016) stated that entrepreneurial efficacy is a determining factor for business success.…”
Section: Discussionsupporting
confidence: 90%
“…This strengthens the fact that entrepreneurial efficacy builds a mindset that fosters the Millennials' intention. Similar findings were obtained by Dwijayanti (2015) and Wirawati et al (2018). Furthermore, Wahyudiono (2016) stated that entrepreneurial efficacy is a determining factor for business success.…”
Section: Discussionsupporting
confidence: 90%
“…Besides, the social mission learning model can improve the learning quality in the classroom. Dwijayanti (2017), Lestari, S. K., & Ningrum (2016) confirmed that the entrepreneurship learning model has a significant effect on entrepreneurial interests. Also, Farida et al (2017), Ginting (2016), Nurwahyuni (2018), Rahmania (2015), Suratman (2017), and Trisnawati (2017) indicated that practice learning model such as social mission is one of the learning strategies that started with solving problems by real context.…”
Section: Discussionmentioning
confidence: 60%
“…The preparation of learning modules covers the scope of entrepreneurship, the determination of ideas and entrepreneurial opportunities, business plans, innovation and creativity in entrepreneurship, management concepts in entrepreneurship, marketing strategies and the concept of Break-Even Point (BEP), subjects of entrepreneurial ethics, entrepreneurial mindset, competitive strategy, motivational theory in entrepreneurship, risk management of customer behaviour and the path to successful entrepreneurship at Sriwijaya University (Firmansyah and Rusmin, 2018), Evaluation of the apprenticeship learning model in increasing student entrepreneurial interest in Universitas Pendidikan Indonesia (Mulyadi et al, 2018), Evaluation of leadership entrepreneurship education at Telkom University Indonesia (Yosephine and Astri, 2017), Effect of EEPS and Academic Support on Student Entrepreneurship Intention at ASMI Multimedia Business Institute (Alfiyan et al, 2019), EEPs in several higher education in Semarang City still focuses on cognitive aspects (Martien Herna Susanti, 2013), Evaluation EEPs with additional variables attitudes and self-efficacy affect student entrepreneurship intentions Kuningan University (Sumarno et al, 2018), Evaluation of EEPs at Surabaya State University has a significant effect on student entrepreneurial attitudes (Dijayanti, 2017), Evaluation of EEPs based on technopreneurship with integration between entrepreneurship study programs that build entrepreneurial competencies at Riau University (Sumarno et al, 2018), EEPs at PGRI Kediri University can improve student character (Arifin and Prasetyaningtyas, 2018), Evaluation of entrepreneurship-based curriculum has a significant impact on non-interest student entrepreneurship economics faculty at the University Computer Indonesia (Mbetwa, 2017), Evaluate the development of training models that effectively build graduates' competencies in entrepreneurship at Semarang State University (Sudana et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…(Yordanova and Filipe, 2019) Answering the problem of unemployment in Indonesia, EEPs needs to be managed more seriously and transformed not just to change the mindset of society into a more concrete program as term solution. Research has proven the success of EEPs in changing EM in Indonesia, among others, have been carried out by (Arifin and Prasetyaningtyas, 2018), (Alfiyan et al, 2019), (Dijayanti, 2017), (Rusmana, 2020), (Indriyani, 2018), (Wijayanto and Prasetyo, 2018), (Santy et al, 2017), (Rimadani and Murniawaty, 2019), (Purusottama and Trilaksono, 2019). The answer is, do EEPs in Indonesia's higher education only stop at the formation of EM?…”
Section: Literature Reviewmentioning
confidence: 99%